Предмет: Алгебра,
автор: блондинка121
(m^2+n-4)^2-(m^2+n-1)(m^2+n-8) упростите выражение
Ответы
Автор ответа:
0
Заменяем (m^2+n-8)=t
Имеем (t+4)^2-(t+7)*t=
=t^2+8t+16-t^2-7t=t+16
Обратная замена t=(m^2+n-8)
m^2+n-8+16=m^2+n+8
Имеем (t+4)^2-(t+7)*t=
=t^2+8t+16-t^2-7t=t+16
Обратная замена t=(m^2+n-8)
m^2+n-8+16=m^2+n+8
Похожие вопросы
Предмет: Алгебра,
автор: ariannanot
Предмет: Английский язык,
автор: Аноним
Предмет: Другие предметы,
автор: andrii727
Предмет: Литература,
автор: gupa
Предмет: Литература,
автор: уирвбзжуцй